1997
DOI: 10.1002/elps.1150180706
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic characterisation of fractions collected from gluten protein extracts subjected to size‐exclusion high‐performance liquid chromatography

Abstract: Electrophoretic characterisation of fractions collected from gluten protein extracts subjected to size-exclusion high-performance liquid chromatographyThe electrophoretic analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE; reduced and unreduced) of fractions, collected from a size exclusion-high performance liquid chromatography (SE-HPLC) separation of gluten proteins using a column with pore size of around 400A, showed clear resolution for the seven elution ranges studied in two A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 8 publications
6
55
2
Order By: Relevance
“…By analyzing only one variety, it was possible to avoid any effects due to genetic variation. The relationship has been confirmed by collecting fractions of glutenin from SE-HPLC and showing that the HMW-GS/LMW-GS ratio increases, as the MW of glutenin increases (Larroque et al, 1997). Thus, the change in balance of dough properties (higher strength, lower extensibility) which is accentuated as the S deficiency becomes more acute, is caused by the shift in MWD to higher MWs.…”
Section: Sulphur Availabilitymentioning
confidence: 79%
“…By analyzing only one variety, it was possible to avoid any effects due to genetic variation. The relationship has been confirmed by collecting fractions of glutenin from SE-HPLC and showing that the HMW-GS/LMW-GS ratio increases, as the MW of glutenin increases (Larroque et al, 1997). Thus, the change in balance of dough properties (higher strength, lower extensibility) which is accentuated as the S deficiency becomes more acute, is caused by the shift in MWD to higher MWs.…”
Section: Sulphur Availabilitymentioning
confidence: 79%
“…1b) show a profile described by Lamacchia et al (2007) and by Lamacchia, Baiano, Lamparelli, La Notte, and Di Luccia (2010), with a polymeric protein peak of glutenin at the extreme left of the profile (Large Polymeric Proteins, LPP > 100,000 Da), followed by a large peak of monomeric gliadin (Large Monomeric Proteins, LMP < 100,000 Da) and finally small peaks of albumins and globulins, known as Small Monomeric Proteins (SMP) (Carceller & Aussenac, 2001;Larroque, Gianibelli, Batey, & MacRitchie, 1996;Larroque, Gianibelli, Batey, & MacRitchie, 1997;Tosi et al, 2005).…”
Section: Effect Of the Replacement Of Semolina With Soy Flours On Spamentioning
confidence: 98%
“…These polymer extracts are suitable for further separation on the basis of size by size-exclusion chromatography (SEC) [9]. Improvements in solvent systems [10] and SEC column efficiency have made SEC a rapid technique for characterizing the intact polymer without disulfide bond reduction [11]. Using 0.5% SDS with and without sonication, Gupta et al [12] separated wheat flour proteins into SDS extractable (EPP) and SDS unextractable (UPP) protein fractions and demonstrated that the amount of polymer in the unextractable fraction liberated by sonication correlated with dough strength.…”
Section: Introductionmentioning
confidence: 99%